A Review of Nanotechnology for Treating Dysfunctional Placenta - Jiang, Huabo; Li, Li; Zhu, Dan; Zhou, Xinyao; Yu, Yongsheng; Zhou, Qian; Sun, Luming (Frontiers in Bioengineering and Biotechnology, 2022)
The placenta plays a significant role during pregnancy. Placental dysfunction contributes to major obstetric complications, such as fetal growth restriction and preeclampsia. Currently, there is no effective treatment for placental dysfunction in the perinatal period, and prophylaxis is often delivered too late, at which point the disease manifestation cannot be prevented. However, with recent integration of nanoscience and medicine to perform elaborate experiments on the human placenta, it is expected that novel and efficient nanotherapies will be developed to resolve the challenge of managing placental dysfunction. The advent of nanomedicine has enabled the safe and targeted delivery of drugs using nanoparticles. These smart nanoparticles can load the necessary therapeutic substances that specifically target the placenta, such as drugs, targeting molecules, and ligands. Packaging multifunctional molecules into specific delivery systems with high targeting ability, diagnosis, and treatment has emerged as a novel theragnostic (both therapeutic and diagnostic) approach. In this review, the authors discuss recent advances in nanotechnology for placental dysfunction treatment. In particular, the authors highlight potential candidate nanoparticle-loaded molecules that target the placenta to improve utero-placental blood flow, and reduce reactive oxygen species and oxidative stress. The authors intend to provide basic insight and understanding of placental dysfunction, potential delivery targets, and recent research on placenta-targeted nanoparticle delivery systems for the potential treatment of placental dysfunction. The authors hope that this review will sensitize the reader for continued exploration of novel nanomedicines.